2021
DOI: 10.3389/fmed.2021.685926
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mosquito Collection Methods for Dengue Surveillance

Abstract: Several methods exist to collect and assess the abundance of dengue vector mosquitoes, i.e., morning adult collection, pupal collection, ovitraps, human landing, and larval collection. Several of these methods are officially implemented to monitor mosquito density and make decisions on treatments for dengue control. This monitoring is also constrained by the need to conduct this assessment on a “one point/one day” process, meaning that once the threshold of 100 households is reached, the assessment is made, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…This limitation was due to the larva’s ability to escape rapidly from sight and its capacity to remain submerged for a long period [ 48 ]. Moreover, vector surveillance is usually conducted for a short period, and sampling techniques have not been standardized among surveyed areas, so the data collected varied and could generate biases [ 44 , 49 ]. Several studies comparing the correlation between mosquito surveys and larvae surveys with dengue incidence showed that mosquito surveys could provide more accurate data to predict impending dengue outbreaks, both spatially and temporally [ 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This limitation was due to the larva’s ability to escape rapidly from sight and its capacity to remain submerged for a long period [ 48 ]. Moreover, vector surveillance is usually conducted for a short period, and sampling techniques have not been standardized among surveyed areas, so the data collected varied and could generate biases [ 44 , 49 ]. Several studies comparing the correlation between mosquito surveys and larvae surveys with dengue incidence showed that mosquito surveys could provide more accurate data to predict impending dengue outbreaks, both spatially and temporally [ 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mosquito breeding place is in a pool of water accommodated in a place or container (Triwahyuni et al 2020). Humidity, environmental conditions, and rainfall have a significant influence on the incidence of DHF, where increased rainfall and humidity are in line with the increase in cases of DHF (Garjito et al 2021;Ghiffari et al 2021;Attaullah et al 2023). According to Alfiyanti and Siwiendrayanti (2021), the distribution of DHF cases is more prevalent in low-altitude plains and areas of high population density.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquito samples were collected once a month and twice a day, between 9:00 and 11:00 a.m. and 1:00 and 2:30 p.m. The sticky pad (square paper pad: 20 cm x 20 cm) method and the sweep net (30 cm in diameter) method were used to capture adult mosquitoes 26,27 . The data were collected by imagining a star-shaped walking route with five points and multiplying it by five to find the center of a circle (5 m in diameter) using a GPS (UTM) device.…”
Section: Sampling Methodsmentioning
confidence: 99%